THE RESULTS OF THE STUDY OF HETEROSIS HYBRIDS OF TOMATO IN THE OPEN FIELD IN NONRCHERNOZEM ZONE OF RUSSIA - I. U. Kondratieva (Овощи России, 2015)
Development of F1 hybrids of tomato for open ground at the moment is one of the main tasks.  It can be solved  only if there are parent forms with valuable features  and properties.  As a result of three years of research  of tomato hybrid combinations and parental lines in the open field in the non6chernozem zone; the heterosis on major economic traits has been revealed. The character  of inheritance of studied traits and the degree of dominance have been determined. The groups of hybrid combinations  with high heterosis  effect and parental lines that contribute to this effect were identified.